STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SDN MANTINGAN - Siti Ari Mursalina; Safikin; Siti Khanifah; Wahyuni Rahma Dianti; Ngurah Ayu Nyoman Murniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education in the 21st century faces increasingly complex and dynamic challenges. One of the big challenges in the world of education is the ongoing curriculum changes, in this case the Merdeka Curriculum. School principals have an important role as leaders who must be able to manage change and ensure that the learning process runs in accordance with curriculum objectives as an effort to improve the quality of education in Indonesia. Therefore, appropriate strategic planning is needed to overcome future problems. The aim of this research is to determine the principal's strategy in improving the quality of education at SDN Mantingan. The focus of this research is on the strategies implemented by school principals to improve the quality of education. The research results show that the principal at SDN Mantingan shows visionary leadership in integrating the values ​​of environmental sustainability and health into the education system. Through the Adiwiyata school program, all elements work together and are involved in the success of the program. However, the obstacles that emerged, including budget limitations, lack of awareness among the school community, and resistance to change, were successfully overcome through innovative approaches, training and ongoing outreach.